EVALUATION OF TEA HERBAL BASED INGREDIENTS CLOVE LEAVES (Syzygium aromaticum) OF MALUKU INDONESIA - Letlora, Marsya Elsina; Baharuddin, Alifia Audy; Wael, Syahran; Jaber, Zaid Mohamad; Rehena, Johanis Fritzgal (RUMPHIUS, 2024)
Clove (Syzygium aromaticum) is one of the famous ancient spices and was used before christ. This plant belongs to the Myrtaceae family which is believed to be able to treat a variety of diseases. Cloves grow in tropical areas and range in height from 10-20 meters and are native plants that originated in Maluku. Clove that can be processed into a drink such as one is to make herbal tea from clove leaves. The type of research used is the experimental type, which is a study conducted to determine the results of organoleptic tests and compunds on clove leaf herbal tea. This research was conducted from July 29 to August 9, 2024 at the Basic Biology laboratory of Pattimura University. The results of the study showed that clove leaf herbal tea has a unique color, aroma and taste and meets quality standards because it has been tested at the level of color, aroma and taste preference. In the color of clove leaf herbal tea, it can be seen that the one ( very like) consists of 7 panelists, the result (like) consists of 3 panelists. Aroma it can be seen that for those who answered (very liked) consisting of 5 panelists, the result of the score (like) consisted of 1 panelist and the result (moderately) consisted of 4 panelists. For the results of the taste score, it can be seen that (very liked) consisted of 1 panelist, the result of the score (liked) consisted of 4 panelists, and the result of the score (moderate) consisted of 4 panelists and for the result of the score (disliked) consisted of 1 panelist. The results of the study showed that clove leaf herbal tea has a unique color, aroma and taste and meets quality standards because it has been tested at the level of color, aroma and taste preference. In the color of clove leaf herbal tea, it can be seen that the one ( very like) consists of 7 panelists, the result (like) consists of 3 panelists. Aroma it can be seen that for those who answered (very liked) consisting of 5 panelists, the result of the score (like) consisted of 1 panelist and the result (moderately) consisted of 4 panelists. For the results of the taste score, it can be seen that (very liked) consisted of 1 panelist, the result of the score (liked) consisted of 4 panelists, and the result of the score (moderate) consisted of 4 panelists and for the result of the score (disliked) consisted of 1 panelist.